0
$\begingroup$

Prove that $$\left(a-b\right)^2\cos^2 \left(\frac{C}{2}\right) + \left(a+b\right)^2\sin^2\left(\frac{C}{2}\right)=c^2$$

My solution:-enter image description here

I don't know what to do next..please give some hint. Or point out if I am wrong somewhere..

$\endgroup$
  • 1
    $\begingroup$ :you forgot to write coeffeciients of Cos$C$ . $\endgroup$ – P.Styles Aug 18 '16 at 4:48
3
$\begingroup$

$$\text{L.H.S}=(a^2 +b^2)\left(\cos^2 \frac{C}{2} +\sin^2\frac{C}{2}\right)-2ab\left(\cos^2 \frac{C}{2} -\sin^2\frac{C}{2}\right)$$ $$=a^2 +b^2 - 2ab\cos C =c^2$$

$\endgroup$
1
$\begingroup$

Using the Cosine, and "double angle" formulas we have:$$(a-b)^2\cos^2(\frac{C}{2})+(a+b)^2\sin^2(\frac{C}{2})=(a-b)^2\left(\dfrac{1+\cos C}{2}\right)+(a+b)^2\left(\dfrac{1-\cos C}{2}\right)=\dfrac{(a-b)^2+(a+b)^2}{2}+\dfrac{(a-b)^2-(a+b)^2}{2}\cdot \cos C=a^2+b^2-2ab\cos C = c^2$$

$\endgroup$
0
$\begingroup$

By Mollweide’s Formulae

\begin{align*} \frac{a-b}{c} &= \frac{\sin \frac{A-B}{2}}{\cos \frac{C}{2}} \\ \frac{a+b}{c} &= \frac{\cos \frac{A-B}{2}}{\sin \frac{C}{2}} \\ \end{align*}

We have $$\left( \frac{a-b}{c} \right)^2 \cos^2 \frac{C}{2}+ \left( \frac{a+b}{c} \right)^2 \sin^2 \frac{C}{2}=1 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.